If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3t + 14 = -2t + -16 Reorder the terms: 14 + 3t = -2t + -16 Reorder the terms: 14 + 3t = -16 + -2t Solving 14 + 3t = -16 + -2t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '2t' to each side of the equation. 14 + 3t + 2t = -16 + -2t + 2t Combine like terms: 3t + 2t = 5t 14 + 5t = -16 + -2t + 2t Combine like terms: -2t + 2t = 0 14 + 5t = -16 + 0 14 + 5t = -16 Add '-14' to each side of the equation. 14 + -14 + 5t = -16 + -14 Combine like terms: 14 + -14 = 0 0 + 5t = -16 + -14 5t = -16 + -14 Combine like terms: -16 + -14 = -30 5t = -30 Divide each side by '5'. t = -6 Simplifying t = -6
| 3x+3=72 | | 6z-2=5z+6 | | 2x+45=x+30 | | 3(x+5)-3(-8x-7)=-45 | | 9x+7=7x-17 | | (2n-5)=4n-1 | | 6x+7y=14 | | 7y+10=9y-10 | | 12x+(-5)=-41 | | 3(x+2)-2(x-1)=8 | | 13z+1=14z-6 | | a-9=20 | | -7-(-17)= | | 5(x-3)=9x-17 | | 8z-5=7z+1 | | b^2+8b-35=0 | | x+7=6x+3 | | -2(y-3)=2y-6 | | -9(9-5y)= | | (x+2)=5 | | 4x^2-8x-21=0 | | 7=-(5-m)+4(6-m) | | 3(x-3)=3x | | 256-6x=39x+16 | | 8-7x=173-42x | | -166-10x=10x+24 | | 14.9p=74.5 | | 0.35*(1059.25+x)=x | | 3x+11=-199-10x | | 4(x+10)+15+x=80 | | -17-3x=13-9x | | 102-6x=10x+22 |